A Multi-Functional Electrolyte for Lithium-Ion Batteries: I. Non-Boiling Electrochemical Performance. Issue 9 (9th July 2016) - Westhoff, Kevin; Bandhauer, Todd
Abstract : In the current two-part study, a new thermal management system for lithium-ion batteries that utilizes multi-functional electrolyte (MFE) with volatile co-solvents is investigated. For this system to function, new electrolyte mixtures that contain high vapor pressure co-solvents are needed. In the present investigation, the characteristics of a previously unstudied high vapor pressure co-solvent HFE-7000 (65 kPa at 25°C) in an MFE (1 M LiTFSI in 1:1 HFE-7000/EMC) are examined. In part I, non-boiling electrochemical performance of the MFE is determined by conductivity, stability window on a glassy carbon electrode, half and full cell cycling with LiFePO4, Li4 Ti5 O12, and Cu2 Sb, and impedance spectroscopy measurements. The results show that the MFE has improved stability compared to a carbonate-only electrolyte and a higher ionic conductivity than other previously investigated electrolytes with hydrofluoroether co-solvents. The MFE-containing cells also had higher impedance than cells with the carbonate-based electrolyte due to lower ionic conductivity. The cells with MFE could not form a stable passivation layer on the LiFePO4 above 3.8 V, and the full Cu2 Sb/LiFePO4 cells were limited by the anode. However, in spite of higher impedance, the remaining cells with low surface tension MFE had higher capacity than for cells with the carbonate electrolyte.